2020
DOI: 10.3390/brainsci10010051
|View full text |Cite
|
Sign up to set email alerts
|

A New Treatment Opportunity for DIPG and Diffuse Midline Gliomas: 5-ALA Augmented Irradiation, the 5aai Regimen

Abstract: Prognosis for diffuse intrinsic pontine glioma (DIPG) and generally for diffuse midline gliomas (DMG) has only marginally improved over the last ~40 years despite dozens of chemotherapy and other therapeutic trials. The prognosis remains invariably fatal. We present here the rationale for a planned study of adding 5-aminolevulinic acid (5-ALA) to the current irradiation of DIPG or DMG: the 5aai regimen. In a series of recent papers, oral 5-ALA was shown to enhance standard therapeutic ionizing irradiation. 5-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Microarray analysis of tumor tissues following 5-ALA and X-ray treatment showed that GO terms, including 'immune response' and 'defense response', and genes related to MHC class I were slightly up-regulated in the X-ray treatment group and highly up-regulated in the 5-ALA and X-ray treatment group [6]. Thus, RDT with 5-ALA is expected to stimulate the immune system more than RT alone and has the potential to further our efforts to "harness synergistic biology between radiation and immunotherapy" [23].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Microarray analysis of tumor tissues following 5-ALA and X-ray treatment showed that GO terms, including 'immune response' and 'defense response', and genes related to MHC class I were slightly up-regulated in the X-ray treatment group and highly up-regulated in the 5-ALA and X-ray treatment group [6]. Thus, RDT with 5-ALA is expected to stimulate the immune system more than RT alone and has the potential to further our efforts to "harness synergistic biology between radiation and immunotherapy" [23].…”
Section: Discussionmentioning
confidence: 98%
“…PpIX has the ability of ROS generation under X-ray irradiation [22]. However, a robust physics-based explanation for the 5-ALA-PpIX radiosensitizing effect is currently lacking [23]. One of the characteristics of PpIX as a photosensitizer is its ability to undergo photobleaching [24,25].…”
mentioning
confidence: 99%
“…A prerequisite for sonodynamic therapy to be effective is, of course, evidence that the sonosensitizer accumulates in tumor cells. It has been widely demonstrated that 5-ALA has preferential uptake in gliomas [37] , pediatric brain tumors [38 , 39] , and DIPG [40] . At the FUSF DIPG workshop, Dr. Javad Nazarian's team shared that not only does 5-ALA, an FDA approved sonosensitizer, accumulate in higher amounts in DMG cells compared to C6 rat glioma models, but also that the DMG cells retain the 5-ALA and produce PpIX for longer amounts of time [13] .…”
Section: Preclinical Studies In Dmg Modelsmentioning
confidence: 99%
“…Although all of the aforementioned studies on PDT efficacy have been performed on adult CNS tumors, pre-clinical and clinical studies have also been performed evaluating the performance of PDT in pediatric brain tumors via second-generation PSs such as 5-ALA and TS [217][218][219]. One of the most recent reports evaluating PDT feasibility for malignant pediatric brain tumors has reported on treatment using TS in children and young adolescents with brain tumors, including diffuse midline glioma (DMG), glioblastoma, and high-grade glioma.…”
Section: Pdt In Other Cns Tumorsmentioning
confidence: 99%